Underwater Adhesion and Anti‐Swelling Hydrogels. Issue 6 (11th November 2022) - Wang, Siying; Liu, Jingying; Wang, Leichen; Cai, Hao; Wang, Qian; Wang, Wenjun; Shao, Jinjun; Dong, Xiaochen
Abstract: Wearable devices, biomaterials, and tissue engineering have all gained from the development of flexible materials. Hydrogels are made up of the polymer matrix in an amount of water and are now being explored extensively. Ascribed to their high hydrophilicity, conventional hydrogels are difficult to deal with high humidity, being easily swell and even decompose. The utilization of hydrogel underwater is influenced by two key factors: the hydrogel absorbs water and swells easily to depress the mechanical characteristics, and the hydration layer at the contact interface also prevents the hydrogel from making close contact with the target surface, preventing conformal and accurate smart perception. So far, many researchers have proposed satisfying improvements for underwater applications from these two perspectives. This review first summarizes the general mechanisms of underwater adhesion hydrogels. Then, various anti‐swelling strategies of the reported hydrogel are described. Finally, the existing challenges and prospects of underwater adhesion and anti‐swelling hydrogels are provided. Abstract : This review first briefly introduces the crucial design principles of underwater applicable hydrogel from the perspectives of fundamental interactive mechanisms of underwater adhesion and anti‐swelling. Secondly, the advantages and disadvantages of different mechanisms of adhesion and anti‐swelling are summarized respectively. Finally, some future opportunities are presented.